HUBUNGAN PEMBERIAN INFORMED CONSENT DENGAN SELF EFFICACY PASIEN PRE KATETERISASI JANTUNG DI RS JANTUNG HASNA MEDIKA - Dwiyanti Purbasari; Nani Yunita; Uni Wahyuni (Jurnal Kesehatan Mahardika, 2018)
Coronary artery disease or CAD is one of the heart disease that the heart couldn’’t pump the blood effectively. That condition leading to ineffective blood perfussion in to the organ. CAD could be detected by coroner catheterization. The first thing to do before performing that is informed consent, besides for communication process between doctor and patient, also impacted on patient thrust in form of self efficacy. Someone with low self efficacy assume them self couldn’t do anything. therefore need a study to know correlation between informed consent and patient self efficacy pre coroner catheterization. This study is quantitative study with descriptive corelational design and cross sectional study. Sample choosen by total sampling method. This study performed in 15 until 30th June 2017 with 30 respondent The result of this study is most of the respondent (23 respondent) completed informed consent, 18 respondent (60%) have positive self efficacy. Spearmen rank statistical study show there is correlation between informed consent and patient self efficacy with pre operative heart catheterization in Hasna Medika Hospital showed by p = 0,0336 (α = 0,05). Beside taht, the correlation between two variable have possitive correlation with mediate correlation that showed by r = 0,384. Informed consent raise patient self efficay in pre operative heart catheterization